Свидетели истории: история денеж. знаков / А. А. Щелоков - Щелоков Александр Александрович (Эврика, 1987)
Экземпляры: ЧЗ (20181002) / Инвентарный номер: 17510 / Цена: 0.40 / Сис.шифр: 63.221 / Авт.знак: Щ 46 / ГРНТИ: 03 / ББК: 63.221(2)